Mineral Profile and Metabolic Status of Cattle in Western Undulating Zone of Odisha - Panda, M.; Panda, N.; Panigrahi, B.; Swain, R.K.; Mishra, A. (Indian Journal of Animal Nutrition, 2018)
Feeds, fodders and serum of cows were collected from 8 villages of two districts of western undulating zone of Odisha and analysed for macro and micro mineral contents. Metabolic profile of animals was also assessed. Among the fodders, paddy straw was found to be deficient in Ca, P and Mn. Rice bran and GN cakehad higher P content. The content of Mn, Cu and Zn in different feeds and fodders varied between 17.14-54.29, 4.55-38.90 and 17.51-47.78 ppm, respectively whereas Fe content in the feeds was above 100 ppm. From theserum profile study, it was found that the animals were deficient in Ca, P, Mg, Zn and Cu to the extent of 72.0, 55.43, 55.05, 50.38 and 42.60%, respectively. Only 8.0 and 13.15% of the animals showed less serum Fe and Mn concentration, respectively. The serum glucose, protein, albumin, globulin and cholesterol levels of the animals were 44.58 mg/dL, 4.67 g/dL, 2.21 g/dL, 2.46 g/dL and 60.04 mg/dL, respectively. It was suggested that supplementation of minerals like Ca, P, Mg, Zn and Cu along with protein rich feed should be given in the diet of the cattle for better health and productivity in this zone.